2019
DOI: 10.2459/jcm.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

The BIOFLOW-III Italian Satellite Registry: 18-month results of the Orsiro stent in an all-comer high-risk population

Abstract: Aims We aimed to corroborate clinical evidence on the safety and efficacy of the ultrathin-strut biodegradable-polymer sirolimus-eluting Orsiro stent in an all-comer population including high-risk subgroups. Methods The nationwide, prospective, all-comer BIOFLOW-III Satellite Registry was conducted at 18 Italian sites. High-risk subgroups [diabetes, small vessels (≤2.75 mm), acute myocardial infarction (AMI), and chronic total occlusions (CTOs)] were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…This rate is on par with the 0.5% definite/probable stent thrombosis documented in the BIOFLOW-III Italian Satellite registry. 23 Additionally, this is comparable to the T-FLEX registry, 24 Thailand Orsiro registry, 25 and BIONYX trial, 26 which reported rates of definite/probable stent thrombosis as 0.6%, 0.7%, and 0.7%, respectively. The SORT OUT IX trial 27 reported 1.1% definite/probable stent thrombosis, which is numerically more than double that observed in the present registry at the 1-year follow-up.…”
Section: Discussionsupporting
confidence: 62%
“…This rate is on par with the 0.5% definite/probable stent thrombosis documented in the BIOFLOW-III Italian Satellite registry. 23 Additionally, this is comparable to the T-FLEX registry, 24 Thailand Orsiro registry, 25 and BIONYX trial, 26 which reported rates of definite/probable stent thrombosis as 0.6%, 0.7%, and 0.7%, respectively. The SORT OUT IX trial 27 reported 1.1% definite/probable stent thrombosis, which is numerically more than double that observed in the present registry at the 1-year follow-up.…”
Section: Discussionsupporting
confidence: 62%
“…During the study period, the SES was made available in lengths of 8,12,16,20,24,28,32,36,40,44, and 48 mm and diameters of 2.00, 2.25, 2.50, 2.75, 3.00, 3.50, 4.00, and 4.50 mm.…”
Section: Highlightsmentioning
confidence: 99%
“…It is reported that the incidence of stent thrombosis has been decreasing, owing to the improvement of stent design and procedures [17,18]. Although the reported incidence of stent thrombosis varies depending on clinical settings and definitions, the reported incidences have been decreasing to <1% [19,20]. In addition, there are several procedurerelated factors that affect the incidence of stent thrombosis, not just post-PCI antithrombotic treatment.…”
Section: Discussionmentioning
confidence: 99%